The Influence of the Kick Ball Training Method on the Sepak Takraw Passing Skills of Undikma Mataram 2024 Athletes - Nurdin, Nurdin; Lukman, Lukman (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Practice using the method kickball towards skills passing This is a very suitable exercise to strengthen first ball control, so that when counterattacking against the opponent it can be done easily. Practice using kickball This can also hone the endurance in the legs, so that they can handle the ball well according to what is desired. Mataram Undikma athletes still have many weaknesses in ball control when performing passing So the researchers wanted to examine Undikma Mataram athletes in controlling the ball while performing passing in the sepak takraw game, in a match especially in the city Mataram as for the aim of this research is to determine the effect of method training kickball Against Skills Passing Sepak Takraw for Undikma Mataram Athletes in 2024. The research design used was experimental research and the static group pretest-posttest design. This type of research uses research by providing treatment (treatment), in the form of training methods kickball towards skills passing sepak takraw, this research uses instrument namely tests passing sepak takraw, so that the research sample uses the entire population to be used as the research sample, namely all 20 Undikma Mataram Athletes with a sampling technique using technique population studies. The results of research and data analysis carried out using statistical formulas show that the calculated t-value is greater than the t-table, (3.482>2.093) thus the